ANALISIS PERBANDINGAN APBD DALAM PERSPEKTIF OPTIMALISASI REALISASI ANGGARAN DAN PERHITUNGAN ANGGARAN SISA LEBIH (SiLPA) KEUANGAN PEMERINTAH KOTA PEKALONGAN TAHUN PEMBIAYAAN 2017-2020 - Maria Evana; Agus Munandar (Jurnal Akuntansi, 2022)
This research activity is for a comparative analysis of the budget in the perspective of optimizing budget realization and calculating the remaining budget (SiLPA) of the Pekalongan city government’s finances for the 2017-2020 fiscal year. Using five ratio analysis to calculate it, namely the degree of decentralization, independence ratio, effectiveness ratio, efficiency ratio and growth ratio. This study concludes that the average degree of decentralization in 2017-2020 is 15.45%, the results of regional financial independence have a consultative relationship, regional financial capacity is still low on development in paying regional taxes and levies, the results of the effectiveness and effective efficiency ratios, the ratio average PAD growth of 2.29%, total revenue of 3.37% and spending growth of 2.85%, there was a decrease in the number of SiLPA from 2017-2019 but there was an increase again in 2020 by 2%. Keyword: Effectiveness, Efficiency, Rationality, SiLPA